80.5k views
5 votes
7(2p+3)-8=6p+29
Please some help me solve this equation with steps.

User Murraybo
by
6.7k points

2 Answers

5 votes

7(2p + 3) -8 = 6p + 29 \\

Simplify both sides of the equation.


14p + 13 = 6p +29

Subtract both sides by 6.


14p + 13 - 6p = 6p + 29 - 6p \\ 8p + 13 = 29

Subtract both sides of the equation by 13.


8p + 13 - 13 = 29 - 13 \\ 8p = 16

Divide both sides by 8.


(8p)/(8) = (16)/(8) = p = 2

User Franklinsijo
by
7.2k points
2 votes
So,

First, I'd like to note that it is required to show work. You shouldn't need to ask for steps.

7(2p + 3) - 8 = 6p + 29

Distribute
14p + 21 - 8 = 6p + 29

Collect Like Terms
14p + 13 = 6p + 29

Subtract 6p from both sides
8p + 13 = 29

Subtract 13 from both sides
8p = 16

Divide both sides by 8
p = 2

Check
7(2(2) + 3) - 8 = 6(2) + 29

Simplify inside the parentheses first.
7(4 + 3) - 8 = 6(2) + 29
7(7) - 8 = 6(2) + 29

Now, distribute.
49 - 8 = 12 + 29

Collect Like Terms
41 = 41 This checks.

S = { 2 }
User Tuhin Bepari
by
8.5k points